TURNOVER OF PUBLIC SECTOR EMPLOYEES AND THE MEDIATING ROLE OF JOB SATISFACTION: AN EMPIRICAL STUDY IN LATVIA - Ludviga, Iveta; Senņikova, Irina; Kalviņa, Agita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Public sector reforms in many countries have been related to cost reductions, increased workload and similar issues. Ignoring the impact of reforms on employee job satisfaction may decrease employee engagement and the quality of service delivery. This paper aims to identify the main factors that determine the level of job satisfaction of public sector employees in a developing country and to find out which factors should be addressed first in order to decrease employee turnover. The survey conducted in 2015 included 365 respondents. For data analysis, partial least square structural equation modelling (PLS-SEM) technique is used to test the model and identify the most important factors relevant to turnover intentions. The results indicate a strong relationship between satisfaction factors and intentions to stay. Satisfaction partly mediates the association between career growth possibilities, work environment, attitude of a direct manager, pay as well as social security and intentions to stay. Growth has the strongest total effect on intentions to stay with a public sector organisation. Thus, taking into consideration the cost cuttings and economic situation, career growth and the reward system are the two factors, which should be addressed first. Moreover, pay is the most important factor for the attraction of younger generation employees to the public sector.